2024
DOI: 10.1681/asn.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron and the Risk of Sudden Cardiac Death among Individuals Receiving Maintenance Hemodialysis

Sherin Ismail,
Michele Jonsson Funk,
Jennifer E. Flythe

Abstract: Background: Individuals receiving hemodialysis have high incidence of sudden cardiac death and are susceptible to QT interval prolonging medication-related cardiac complications. Ondansetron, an antiemetic with known QT prolonging potential, is associated with fatal arrythmias in the general population when administered intravenously. The cardiac safety of ondansetron in the hemodialysis population is unknown. Methods: We conducted a new-user, active-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We thank Hung and Chao 1 for their interest in our study and their laudatory comments regarding the importance of the subject and the comprehensiveness of the analysis. 2 In subgroup analyses, we found that patients using at least one other medication with known risk of Torsades de Pointes at the time of ondansetron initiation may have had a lower 10-day relative risk of sudden cardiac death compared with patients not using such medications at the time of ondansetron initiation. Small subgroup sample sizes limited a formal assessment of statistical interaction and also warrant caution when interpreting these findings.…”
mentioning
confidence: 77%
“…We thank Hung and Chao 1 for their interest in our study and their laudatory comments regarding the importance of the subject and the comprehensiveness of the analysis. 2 In subgroup analyses, we found that patients using at least one other medication with known risk of Torsades de Pointes at the time of ondansetron initiation may have had a lower 10-day relative risk of sudden cardiac death compared with patients not using such medications at the time of ondansetron initiation. Small subgroup sample sizes limited a formal assessment of statistical interaction and also warrant caution when interpreting these findings.…”
mentioning
confidence: 77%
“…The focus on a limited number of high-risk medications allowed for more detailed, medication-specific descriptions of prescription and dispensation patterns of medications shown to be associated with a higher risk of sudden cardiac death among people receiving maintenance hemodialysis. 12 , 13 , 14 , 15 We defined new use as a prescription fill for a study medication after a 180-day washout period free of prescription fills for the study drug of interest. Studying new use supported reliable ascertainment of the origin of study prescription medications (ie, prescriber and dispenser) and captured the point in time when the prescriber made the prescribing decision and might have considered medications that were already prescribed to the patient in their decision to prescribe the study medication.…”
Section: Methodsmentioning
confidence: 99%
“…For example, compared with clinically relevant comparator medications, QT-prolonging medications with known risks of torsades de pointes (TdP), such as respiratory fluoroquinolones, azithromycin, ondansetron, and certain selective serotonin reuptake inhibitors, are associated with higher risks of sudden cardiac death in people receiving hemodialysis. 12 , 13 , 14 , 15 This risk is further elevated in the setting of concomitant use of other QT-prolonging medications with known risk of TdP than in the setting of stand-alone use. 12 , 14 Prescriber education programs, 16 , 17 medication reconciliation, 18 , 19 , 20 and electronic health record (EHR) supports 21 , 22 , 23 reduce unsafe prescribing practices in populations not undergoing dialysis.…”
Section: Introductionmentioning
confidence: 99%